2012
DOI: 10.1080/02607476.2012.656444
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Teacher Feedback Observation Scheme: evaluating the quality of feedback in peer groups

Abstract: Research suggests that feedback is an essential element in learning. This study focuses on feedback that teachers provide in reciprocal peer groups to improve their performance in the classroom. The Teacher Feedback Observation Scheme (TFOS) was developed to identify feedback patterns, which approaches feedback as a multidimensional process. The TFOS helps acquire insights into the effectiveness of feedback, and provides information regarding the situations in which possible interventions can be undertaken if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
1
23
0
3
Order By: Relevance
“…Future research can explore feedback processes for instance by means of observation. In an empirical study, we have pilot tested our observational instrument and shown that effectiveness of feedback depends on patterns of feedback instead on one dimensional characteristics (Thurlings, Vermeulen, Kreijns, Bastiaens, & Stijnen, 2012).…”
Section: Future Researchmentioning
confidence: 99%
“…Future research can explore feedback processes for instance by means of observation. In an empirical study, we have pilot tested our observational instrument and shown that effectiveness of feedback depends on patterns of feedback instead on one dimensional characteristics (Thurlings, Vermeulen, Kreijns, Bastiaens, & Stijnen, 2012).…”
Section: Future Researchmentioning
confidence: 99%
“…This observational instrument was called Teacher Feedback Observation Scheme (TFOS) and was piloted in a study by Thurlings, Vermeulen, Kreijns, Bastiaens and Stijnen (2012). Because of the preliminary findings of this pilot study and our experiences with the instrument, we adapted it in two ways.…”
Section: Overview Of Our Previous Workmentioning
confidence: 99%
“…The fourth dimension is positive vs. neutral vs. negative and concerns whether feedback is expressed in a positive way (e.g., providing compliments), in a negative way (e.g., conveying slate or attacking the receivers), or in a neutral way (i.e., neither positive nor negative; e.g., Scheeler et al, 2004). Based on our literature review, we assumed that goal-directed, specific, and detailed feedback that is formulated in a neutral manner is more effective for learning than feedback that is person-directed, general, vague, and formulated either too positive or too negative (Thurlings et al, 2013;Thurlings, Vermeulen, Kreijns et al, 2012). These four dimensions are central in the observation instrument we used.…”
Section: How We Defined Effective Observed Feedback In Our Studiesmentioning
confidence: 99%
See 2 more Smart Citations